Performance Analysis of SNR-Based HDAF M2M Cooperative Networks - Lingwei Xu; Hao Zhang; T. Aaron Gulliver (Journal of Electrical and Computer Engineering)
The lower bound on outage probability (OP) of mobile-to-mobile (M2M) cooperative networks over N-Nakagami fading channels is derived for SNR-based hybrid decode-amplify-forward (HDAF) relaying. The OP performance under different conditions is evaluated through numerical simulation to verify the accuracy of the analysis. These results show that the fading coefficient, number of cascaded components, relative geometric gain, and power-allocation are important parameters that influence this performance.